2015
DOI: 10.1017/s0007114515001890
|View full text |Cite
|
Sign up to set email alerts
|

The Nordic diet and cognition – The DR's EXTRA Study

Abstract: The rapid increase in the prevalence of dementia associated with ageing populations has stimulated interest in identifying modifiable lifestyle factors that could prevent cognitive impairment. One such potential preventive lifestyle factor is the Nordic diet that has been shown to reduce the risk of CVD; however, its effect on cognition has not been studied. The aim of the present study was to estimate the cross-sectional and longitudinal associations of the baseline Nordic diet with cognitive function at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 40 publications
0
28
0
3
Order By: Relevance
“…Previous studies have provided some evidence that a lower intake of polyunsaturated fatty acids (PUFAs) [22,23], a higher intake of saturated fat [24,25], a lower consumption of vegetables and fish [22,23], and a poor adherence to the Mediterranean diet, the Dietary Approaches to Stop Hypertension (DASH) diet, and the Nordic diet [26][27][28][29] may increase the risk of dementia and Alzheimer's disease among adults and older adults. Similarly, increased cardiometabolic risk has been linked to an increased risk of dementia in older adults [30].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided some evidence that a lower intake of polyunsaturated fatty acids (PUFAs) [22,23], a higher intake of saturated fat [24,25], a lower consumption of vegetables and fish [22,23], and a poor adherence to the Mediterranean diet, the Dietary Approaches to Stop Hypertension (DASH) diet, and the Nordic diet [26][27][28][29] may increase the risk of dementia and Alzheimer's disease among adults and older adults. Similarly, increased cardiometabolic risk has been linked to an increased risk of dementia in older adults [30].…”
Section: Introductionmentioning
confidence: 99%
“…The dotted vertical lines correspond to the 10th, 25th, 50th, 75th and 90th percentile of the healthy Nordic diet score These different versions of a healthy Nordic diet have had beneficial associations with several disease risk factors, such as hypertension [8], abdominal obesity and weight gain [5,10,25], inflammation [7] and serum lipids [9], although one study reported an association with decreased HDL cholesterol [26]. Higher adherence to a healthy Nordic diet has also been associated with lower risk of colorectal cancer in women [12], better cognition [27], greater muscle strength and physical capacity in old age [6,28], and with reduced risk of myocardial infarction [15,16], stroke [17], total mortality [11,13,14] and type 2 diabetes [19], although some studies have observed no association with risk of type 2 diabetes [18] or cardiovascular disease [29]. Overall, however, a higher adherence to a healthy Nordic diet appears to be associated with beneficial health outcomes, and our current findings add to the knowledge of the potential health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…(26) A dieta é caracterizada por consumo abundante de vegetais, frutas vermelhas e frutas em geral, peixes e produtos derivados de grãos integrais, bem como consumo baixo a moderado de carne e de álcool, sendo que a principal fonte recomendada de gordura é o óleo de canola. (27) A DMB é rica em compostos como polifenóis e antioxidantes, e os grãos tipicamente utilizados nessa região para a confecção de pães e mingaus, como o centeio, a aveia e a cevada, são ricos em fibras. Além disso, o óleo de canola é fonte de ácidos graxos insaturados.…”
Section: Padrões Alimentares E Suas Característicasunclassified
“…Além disso, o óleo de canola é fonte de ácidos graxos insaturados. (27) Devido a estas características, a adesão à DMB, também conhecida como Dieta Nórdica, tem sido associada à presença reduzida de fatores de risco cardiovascular, (28,29) bem como a um melhor desempenho cognitivo em indivíduos sem perda cognitiva. (27) No que diz respeito à dieta vegetariana, ela é definida como uma dieta que não inclui a ingestão de carne (inclusive frango) ou frutos do mar, nem alimentos contendo esses produtos.…”
Section: Padrões Alimentares E Suas Característicasunclassified
See 1 more Smart Citation